Economic burden of Huntington disease in Europe and the USA: Results from the Huntington's Disease Burden of Illness study. (8th December 2022) - Rodríguez‐Santana, Idaira; Mestre, Tiago; Squitieri, Ferdinando; Willock, Rosa; Arnesen, Astri; Clarke, Alison; D'Alessio, Barbara; Fisher, Alex; Fuller, Rebecca; Hamilton, Jamie L.; Hubberstey, Hayley; Stanley, Cath; et al.
Abstract: Background and purpose: The prevalence of Huntington disease (HD) has increased over time; however, there is a lack of up‐to‐date evidence documenting the economic burden of HD by disease stage. This study provides an estimate of the annual direct medical, nonmedical, and indirect costs associated with HD from participants in the Huntington's Disease Burden of Illness (HDBOI) study in five European countries and the USA. Methods: The HDBOI is a retrospective, cross‐sectional study. Data collection was conducted between September 2020 and May 2021. Participants were recruited by their HD‐treating physicians and categorized as early stage (ES), mid stage (MS), or advanced stage (AS) HD. Data were collected via three questionnaires: a case report form, completed by physicians who collected health care resource use associated with HD to compute direct medical cost, and optional patient and caregiver questionnaires, which included information used to compute nondirect medical and indirect costs. Country‐specific unit cost sources were used. Results: HDBOI cost estimates were €12, 663 ( n = 2094) for direct medical costs, €2984 ( n = 359) for nondirect medical costs, and €47, 576 ( n = 436) for indirect costs. Costs are higher in patients who are at later stages of disease; for example, direct medical costs estimates were €9220 ( n = 846), €11, 885 ( n = 701), and €18, 985 ( n = 547) for ES, MS, and AS, respectively. Similar trends were observed for nondirect and indirect costs. Costs show large variations between patients and countries. Conclusions: Cost estimates from the HDBOI study show that people with HD and their caregivers bear a large economic burden that increases as disease progresses. Abstract : The Huntington's Disease Burden of Illness study provides an estimate of the annual direct medical, nonmedical, and indirect costs associated with Huntington disease (HD) using data from participants in five European countries and the USA. Cost estimates show that people with HD and their families bear a large economic burden that increases as disease progresses.